If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(-2+n)=91+(-n+1)
We move all terms to the left:
5(-2+n)-(91+(-n+1))=0
We add all the numbers together, and all the variables
5(n-2)-(91+(-1n+1))=0
We multiply parentheses
5n-(91+(-1n+1))-10=0
We calculate terms in parentheses: -(91+(-1n+1)), so:We get rid of parentheses
91+(-1n+1)
determiningTheFunctionDomain (-1n+1)+91
We get rid of parentheses
-1n+1+91
We add all the numbers together, and all the variables
-1n+92
Back to the equation:
-(-1n+92)
5n+1n-92-10=0
We add all the numbers together, and all the variables
6n-102=0
We move all terms containing n to the left, all other terms to the right
6n=102
n=102/6
n=17
| 2(x13)-4=12 | | 9x-4=12x+2 | | 8x+31=x | | 44+44+14x-6=180 | | 2m+6=3m-7 | | 4x-2=-17 | | 10u+7=(u-4)-9 | | -3s+4=19-2s | | b/3=4/3 | | 360=12x-4+18x+4+15x+10+5x | | 6w=5w+14 | | -9-10v=-5v+5-7v | | 20u^2-55u=0 | | 6m+10=-2+1 | | -6+6y=-9 | | 20^2-55u=0 | | -9−10v=-5v+5−7v | | 936=(2x-4)(x+8) | | 6y+7=2y+43 | | 7-6b+10=-10-3b | | 1/7x=0.25x-2.75 | | 8(3-6n)=264 | | 12n=3+(2(n+1)) | | -24=-18t | | -8-6-3b-3=b+7 | | (2a+2)÷116=38 | | 6x+10=9x+50 | | x1/2+3/4= | | 6^(x-7)=94 | | 3x(9)=9(x+2) | | 7x-15/6=-6 | | 8(k=3)=12k-4 |